Temperature‐dependent surface charge and discharge behaviour of converter transformer oil–paper insulation under DC voltage. Issue 1 (1st January 2019) - Du, Boxue; Chang, Rui; Zhu, Wenbo; Li, Jin; Jiang, Jinpeng
Abstract : Ambient temperature has significant influence on properties of oil–paper insulation, which makes surface discharge process complex. This paper aims at revealing the influence mechanism of ambient temperature on surface charge and discharge behaviours under DC voltage. The oil–paper with thickness of 0.08 mm was used and the ambient temperature varies from 20 to 80°C in this paper. The results of surface potential decay (SPD) experiments show that the initial surface potential declines and the process of SPD is accelerated with increasing temperature because of higher carrier mobility. Additionally, both shallow and deep trap energy level become deeper, the shallow trap density is enlarged while the deep trap density is shrunken at higher temperature. The surface discharge tests were performed and Weibull results indicate that it is prone to occurring surface discharge at higher ambient temperature. The possibility of surface discharge under negative voltage is larger than that under positive voltage because of polarity effect. It is concluded that more carriers escape from deep traps to participate in the procedure of surface discharge at higher temperature, which declines the surface discharge voltage.